Psychopathological symptoms among men with problem of psychical and physical violence in childhood - Rzeszutko, Ewa; Pawłowska, Beata; Potembska, Emilia; Morawska-Pyter, Agata; Pyter, Tomasz; Kowal, Agnieszka (Current Problems of Psychiatry, 2011)
The aim of this study was to answer the following research problem: whether and in what psychopathological symptoms there are differences between men with problem of psychical and physical violence in childhood and in men without this problem. Among the psychopathological symptoms there are: alcohol abuse, use of psychoactive drugs, depression, disturbed eating attitudes, distorted body image. Material and methods: The study group consisted of 90 men who are second-year medical students. The median age was 22 years. Seventy eight (78) students came from the town and 12 from the village. Thirty eight (38) persons were brought up in a full family, but 52 persons in an incomplete family. Parents of 47 students were divorced, 5 persons were brought up in an incomplete family because of the death of a parent. Psychoactive substances were taken by 33 men, 36 students abused alcohol, and seven admitted to making self-harm. Alcohol abuse by a family member was reported by 20 students, and eating disorders in a family member were reported by 13 men. The study used the personal questionnaire of our own construction and Eating Disorder Questionnarie for Men created by Beata Pawłowska and Zofia Stankiewicz.Results and conclusions: Based on the personal questionnaire, there was selected a group of 28 students who were the victims of psychical violence and a group of 18 men, who were the victims of physical violence in childhood. Research proved a relationship between experiencing of psychical and physical violence in students’ childhood and alcohol abuse, a sense of worthlessness, helplessness, lack of meaning in life, non-adaptational ways of coping, self-harm, negative self-esteem and addiction to exercise.